PENGARUH MASA PERIKATAN AUDIT, ROTASI KAP, UKURAN PERUSAHAAN KLIEN, UKURAN KAP DAN FEE AUDIT PADA KUALITAS AUDIT (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to determine the effect of the audit engagement period, rotation hood, the client company size, the size of the hood and audit fees on audit quality in manufacturing companies listed on the Stock Exchange during the study period 2011-2013. The data obtained from the financial statements of publicly traded companies. The number of samples is 129 manufacturing company. Data analysis method used is logistic regression analysis aimed to test the effect of a variable period of the audit engagement, the firm rotation, the size of the client company, the size of the firm and audit fees to audit quality as the dependent variable in the manufacturing companies listed in Indonesia Stock Exchange (IDX). The results showed a variable period of the audit engagement significant negative effect on the quality of the audit, the firm rotation is not significant positive effect on the quality of the audit, the size of the client companies significant negative effect on the quality of the audit, the firm size is not a significant positive effecton the quality of the audit and the audit fee audit no significant positive on audit quality.Keywords: Tenure Audit, The Firm Rotation, Size of The Client, Firm Size and Fee Audit